Relative bioavailability of salbutamol to the lung following inhalation using metered dose inhalation methods and spacer devices. - Hindle, M. (1994)
BACKGROUND--Inhalation aids do not require coordination between actuation of a metered dose inhaler (MDI) with inspiration and reduce oropharyngeal impaction. The delivery of salbutamol to the lung and systemic availability following inhalation with three commonly used spacers and an open mouth technique have been evaluated using a simple noninvasive technique based on urinary excretion 30 minutes and 24 hours after the dose. METHODS--Ten healthy subjects inhaled, on randomised study days, 4 x 100 micrograms from a Ventolin MDI and, subsequently, with the aid of a Volumatic, Bricanyl Spacer, and Nebuhaler spacer device. In addition, an open mouth inhaler technique was evaluated. Urine samples were collected 0-30 minutes and 0.5-24 hours after inhalation. From these samples the relative bioavailability to the lung (urinary salbutamol excretion 30 minutes after dosing) and the systemic bioavailability of the dose (24 hour urinary excretion of salbutamol and its metabolite) for each inhalation method was obtained. RESULTS--The mean (SD) urinary excretion of salbutamol 30 minutes after inhalation using the MDI alone and with the Volumatic, Bricanyl Spacer, Nebuhaler, and open mouth technique was 2.83 (0.78)%, 3.37 (0.69)%, 4.09 (0.91)%, 4.34 (1.60)%, and 3.49 (0.98)%, respectively, expressed as a percentage of the nominal dose. The nebuhaler and Bricanyl Spacer spacer devices were found to increase the relative bioavailability of salbutamol to the lung compared with the MDI alone. Compared with the MDI the inhalation aid increases were much greater than the intra-individual variability of the urinary excretion method. In 11 individuals who each repeated the same inhalation procedure on four separate occasions, the mean (SD) coefficient of variation was 8.24 (2.36)%. The mean (SD) 24 hour urinary excretion of salbutamol and its metabolites was 26.6 (6.79), 27.0 (7.95), and 55.6 (9.74)% of the salbutamol dose for the Volumatic, Nebuhaler, and MDI, respectively. Similar values following the open mouth method and Bricanyl Spacer were 48.9 (10.97)% and 43.8 (11.57)%. These values, representing the systemic availability of the inhaled dose, were lower when inhaling with the aid of the Volumatic and Nebuhaler than inhalation from the MDI alone. CONCLUSIONS--Spacer devices improve pulmonary bioavailability of salbutamol and reduce the systemically available dose.